Our parents, ourselves : how American health care imperils middle age and beyond - Turiel, Judith Steinberg, 1948- (University of California Press, 2005)
The prospect of caring for elderly relatives who may be too old, fragile, or forgetful to manage on their own looms large for millions of women and men who are unprepared for the difficulties such an experience can bring.